Lifestyle oriented small tourism firms - Carlsen, Jack; Morrison, A.; Weber, Paull (Centre for Tourism Research and Development, 2008)
Small tourism firms in attractive tourism destinations are often generically described as ‘lifestyle’ oriented. A discourse on what the prefix ‘lifestyle’ means, when attached to small tourism firms in different economic and social contexts has been developing for a decade now, reaching a point of complexity and contradiction. In order to explore this ubiquitous, yet nebulous term, the relevant literature and associated discourse is reviewed with the aim of understanding the motives, meanings, values and contexts of these lifestyle oriented small tourism (LOST) firms. It is concluded that there are many deficiencies in both the conceptualization as well as the content of current research in this increasingly important area. A multi-disciplinary and systemic model for understanding the interactions and interdependencies of the different dimensions of LOST firms is presented.